Сервіс-орієнтовані, розподілені системи реального часу в електронних бібліотеках - Новицький, Олександр (Видавництво Львівської політехніки, 2012)
The article reviewed the problem of building service-oriented web applications in real time. In particular for predicting the execution time high-loaded applications, providedstationary load, it is proposed to use the Erlang model with infinite queue length. We also propose a new adaptive algorithm for predicting execution time. As a practical implementation, approved our proposals on a system of converting file formats.
Keywords: сервіс-орієнтовані веб додатки реального часу; модель Ерланга; конвертація форматів файлів